Cushman and Kohut: Constructing Identities vs. Developing Selves in the Context of Modern American Life. Issue 3 (2nd July 2020) - Riker, John H.
ABSTRACT: In this paper I address Phillip Cushman's critique of psychoanalytic psychotherapy as being both naïve about how socio/political forces generate persons in America and complicit in reproducing the deficient form of self generated in America—the "masterful, bounded, empty self, " a kind of self he finds particularly validated in the theories of self psychologists Winnicott and Kohut. I both show how these critiques are misguided and provide a different narrative for why psychodynamic therapy arose, one that sees it not as a pawn of socio/discursive forces, but as an important source of rebellion, one offering an alternative way of being human from the regnant forms dominating modern life. I further show how Kohut's self psychology can help us negotiate the difficult problem of Otherness. In the end, I bring Cushman and Kohut together by seeing Cushman's work as exploring how identities are constructed, while Kohut is articulating a theory of how selves are developed. The crucial conceptual point is to differentiate ego identities from nuclear selves and understand their psychological interdependence.